Formação de hidrogel de alginato de cálcio por congelamento e sua aplicação na captura de microplásticos - Oliveira, Rafael Vinicius de (Universidade Federal de São Carlos, 2025)
Employed in various sectors such as health and agriculture, hydrogels have been gaining prominence for their properties, especially for their high capacity to retain liquids without compromising their structure. Among the different polymers that can constitute hydrogels, alginate stands out in this study, a biopolymer extracted from brown algae. Alginate has the ability to gel when interacting with divalent ions, such as calcium ions. This interaction results in the formation of a calcium alginate hydrogel when there are adequate concentrations of both components involved. The studies presented in this dissertation propose an innovative technique for forming hydrogels at sub-gelling concentrations — concentrations where the hydrogel does not form at room temperature. The methodology developed is based on two main concepts: slow freezing and the ice-template technique. Slow freezing promotes an increase in the concentration of solutes in the medium, favoring the interaction between alginate and calcium ions, while the ice crystals formed perforate the hydrogel, giving the material a porous characteristic. The results obtained showed how the different concentrations of calcium and alginate interfere with hydrogel formation and raised some questions regarding the interactions of the components at sub-gelling concentrations. In addition to the efficiency of this methodology in producing irreversible hydrogels by freezing, its potential to capture particles, such as spray paint microplastics, was demonstrated, something unprecedented so far. With the studies carried out, it is expected to offer a new perspective on hydrogels, opening paths for future research, enhancing the understanding of the use of hydrogels, and the scalability of the technique.
Formation of calcium alginate hydrogel by freezing and its application for microplastic capture
Keywords: Alginato; Captura; Congelamento; Hidrogéis; Microplásticos; Alginate; Capture; Freezing; Hydrogels; Microplastics; CIENCIAS EXATAS E DA TERRA::QUIMICA::QUIMICA ORGANICA::POLIMEROS E COLOIDES